Outcome of transarterial radioembolization in patients with hepatocellular carcinoma as a first-line interventional therapy and after a previous transarterial chemoembolization - Wagenpfeil, Julia; Kupczyk, Patrick Arthur; Bruners, Philipp; Siepmann, Robert; Guendel, Emelie; Luetkens, Julian Alexander; Isaak, Alexander; Meyer, Carsten; Kuetting, Fabian; Pieper, Claus Christian; Attenberger, Ulrike Irmgard; Kuetting, Daniel (Frontiers in Radiology, 2024)
Purpose Due to lack of data, there is an ongoing debate regarding the optimal frontline interventional therapy of unresectable hepatocellular carcinoma (HCC). The aim of the study is to compare the results of transarterial radioembolization (TARE) as first-line therapy and after prior transarterial chemoembolization (TACE) in these patients. Methods 83 patients were evaluated. 38 patients received at least one TACE session prior to TARE (27 male; mean age 67.2 years; 68.4% stage BCLC B, 31.6% BCLC C); 45 patients underwent primary TARE (33 male; mean age 69.9 years; 40% BCLC B, 58% BCLC C). Clinical (age, gender, BCLC stage, activity (GBq), Child-Pugh status, portal vein thrombosis, tumor volume), and procedural (overall survival (OS), local tumor control (LTC) and progression-free survival (PFS)) data were compared. Regression analysis was performed to evaluate OS, LTC and PFS. Results No differences were found in OS (95% CI:1.12, P=0.289), LTC (95% CI:0.003, P=0.95) and PFS (95% CI:0.4, P=0.525). Regression analysis revealed a relationship between Child-Pugh Score (P=0.005), size of HCC lesions (>10 cm) (P= 0.022) and OS; neither prior TACE (Child Pugh B patients; 95% CI:0.120, P=0.729) nor number of lesions (>10; 95% CI:2.930, P=0.087) correlated with OS. Conclusion Prior TACE does not affect outcome of TARE in unresectable HCC. Abbreviations Hepatocellular carcinoma = HCC, transarterial radioembolization = TARE, transarterial chemoembolization = TACE, Barcelona Clinic Liver Cancer staging system = BCLC, progression free survival = PFS, overall survival = OS, local tumor control = LTC